Dosimetric comparison between three-dimensional conformal radiotherapy followed by electron beam boost and volumetric modulated arc therapy using concomitant boost for the heart and cardiac segments in patients with left-sided breast cancer at risk for radiation-induced cardiac toxicity. (March 2022) - Murakami, Yu; Murakami, Yuki; Kamima, Tatsuya; Oguchi, Masahiko; Abo, Natsumi; Takahashi, Taro; Kaneko, Masahiro; Nakano, Masahiro; Matsubayashi, Fumiyasu; Harada, Arisa; Taguchi, Senzo; Hashimoto, Takeo; et al.
Highlights: SIB-VMAT allows significant LAD dose reduction in left-sided breast cancer patients. 3D-CRT + EB can decrease the mean dose to the heart compared with SIB-VMAT. CT-based MHD was developed to identify the patients at potential risk of RICAD. Selection of RT techniques can influence the doses to the heart and cardiac segments. Abstract: Purpose: We aimed to compare dosimetric parameters between three-dimensional conformal radiation therapy followed by electron beam boost (3D-CRT + EB) and volumetric modulated arc therapy using simultaneous integrated boost (SIB-VMAT) in left-sided breast cancer patients. Methods: This study included 57 patients with left-sided breast cancer who underwent SIB-VMAT. All patients had a computed tomography-based maximum heart distance of ≥ 1 cm and were prescribed a dose of 42.56 Gy/16 fractions to the planning target volume and a concomitant-boosted target dose of 53.2 Gy or 51.2 Gy. The 3D-CRT + EB plan was retrospectively created for the purpose of comparison using tangential fields with field-in-field technique followed by electron beam irradiation. Results: The doses to the clinical target volume significantly improved in the SIB-VMAT plans. All dosimetric parameters for the left anterior descending coronary artery (LAD) and LAD middle position (LAD mid) in the SIB-VMAT plans were significantly lower than those for 3D-CRT + EB plans ( P < 0.01), while the doses to the heart, lung, contralateral breast and non-target tissue were decreased in the 3D-CRT + EB plans compared with those in the SIB-VMAT plans (e.g., 1.9 Gy vs. 2.9 Gy; P < 0.001 for the mean dose of heart). Conclusions: SIB-VMAT significantly improved the dose to the target while reducing the doses to the LAD and LAD mid, whereas 3D-CRT + EB significantly decreased the doses to the heart and other organs at risk in patients with left-sided breast cancer at risk for radiation-induced coronary artery disease.